450 LOW LEVELS OF LYSOPHOSPHATIDIC ACID ACETYLTRANSFERASEβ ACTIVITY IN CONGENITAL GENERALIZED LIPODYSTROPHY. (1st January 2005) - Carew, H. T.; Taleban, S.; Dichek, H. L.; Bonham, L.; Hollenback, D.; Brunzell, J. D.
Abstract : Congenital generalized lipodystrophy (CGL) is a rare autosomal recessive disorder characterized by an almost complete absence of metabolically active adipose tissue. A mutation in the gene for lysophosphatidic acid acyltransferase-β (LPAATβ or AGPAT2) at 9q34.3 has been reported in patients of African descent with CGL Type 1 (CGL-1). We evaluated LPAAT activity levels in peripheral blood mononuclear cells (PBMCs) isolated from three adult patients with a history of CGL-1, acute diabetes, bone cysts, hypertension, and hyper-triglyceridemia (ages 33, 55, and 60). We also tested the PBMCs of a 3 year old patient with CGL-1 along with the patient's parents who do not present with CGL, but presumably carry one mutated LPAATβ gene. The PBMCs of 16 healthy individuals and one individual with an unknown type of lipodystrophy served as controls. Samples were tested for LPAAT activity in the absence and presence of an LPAATfl-specific inhibitor. Surprisingly, total LPAAT activity levels in healthy individuals (4.2 ± 2.3 nmol/min/mg protein) were similar to those in CGL-1 patients (4.3 ± 1.5 nmol/min/mg protein). The effect of the LPAATβ inhibitor on the total activity levels, however, was substantially different: 36-71% of the total activity could be inhibited by the LPAAT?? inhibitor in the healthy controls, while only 9-13% of the total activity could be inhibited in the CGL-1 samples. LPAAT activity levels were 2.9 ± 0.2 and 9.0 ± 0.4 nmol/min/mg protein in the heterozygous and non-CGL-1 lipodystrophy subjects, respectively. The inhibitor reduced 44-62% of activity in the heterozygous patients, and 48% in the other lipodystrophy patient. In conclusion, we demonstrate the loss of LPAAT?? specific activity in PBMCs from patients with mutations in both LPAAT?? alleles suggesting a role for LPAATβ in the development of CGL-1.